The implications of management styles on the level of occupational stress in the library setting - Nierras, Marvic C. (2003)
This study focused on examining the relationship between occupational stress and management styles within unit libraries in U.P. Diliman. In order to accomplish this, it was necessary to determine the following: 1) the management styles being employed by the administrators of unit libraries, 2) the level of occupational stress experienced by the staff of these unit libraries and 3) the differences in the level of occupational stress experienced by staff of libraries whose administrators employ different management styles.